Birth stories: Childbirth, remembrance and 'everyday' heritage. (November 2021) - Boyer, Kate; Hunter, Billie; Davis, Angela
Abstract: Based on the work of critical and feminist heritage scholars who have argued that heritage sites need to pay more attention to everyday experience, we argue that the omission of birth stories from mainstream heritage sites is a problem that needs rectifying. Through an analysis of oral histories undertaken with mothers and midwives in mid 20th Century Wales, we trace out key themes on which such a project could focus, highlighting themes of corporeality, emotions and sense of place. We conclude by signaling some of the steps that would be needed to make such a project happen, and suggest that this move would not only extend understanding of "everyday" heritage, but also add greater depth and nuance to how place is narrated within such spaces. Highlights: Extends understanding about childbirth through oral histories of women who gave or attended birth in mid-20th Century Wales. Creates an analytical framework for understanding these memories, focusing on themes of place, emotion and embodiment. Argues that childbirth deserves a place within sites of public memory and commemoration. Argues that commemorating women's experiences of childbirth memories is an important project for feminism.